LA ACCION DEL CALOR Y EL FRIO SOBRE LOS DIVERSOS COMPONENTES DEL ELECTROGRAMA DEL VENTRICULO CARDIACO - ROSENBLUETH, ARTURO; RAMOS GARCIA, J (Laboratorio Bot Mex, S A, Texcoco, EDO, MEX, MEX, 1947)
The electric responses of the cardiac ventricles of dogs, cats, turtles and frogs were recorded monophasically or diphasically and the influence was studied of the flow of direct current (dc) through the recording electrodes In order to be able to use
ASTRON J
Keywords: ACCION, CALOR, FRIO, COMPONENTES, ELECTROGRAMA, VENTRICULO CARDIACO; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA CARDIOVASCULAR